Tick saliva increases production of three chemokines including monocyte chemoattractant protein-1, a histamine-releasing cytokine - Langhansová, H; Bopp, T; Schmitt, E; Kopecký, J (Parasite immunology, 2015)
The effect of Ixodes ricinus tick saliva on the production of various cytokines and chemokines by mouse splenocytes was tested by a cytokine array. We demonstrated a strong upregulation of three chemokines, monocyte chemoattractant protein-1 (MCP-1), thymus-derived chemotactic agent 3 (TCA-3) and macrophage inflammatory protein 2 (MIP-2). MCP-1 could be induced by tick saliva itself. While TCA-3 and MIP-2 are engaged in Th2 polarization of the host immune response associated with tick feeding, MCP-1 may act as a histamine release factor, increasing blood flow into the feeding lesion thus facilitating tick engorgement in the late, rapid feeding phase.
Keywords: Ixodes ricinus; organismy bez specifických patogenů; klíště; Specific Pathogen-Free Organisms; Saliva; Chemokine CCL2; chemokin CCL2; uvolňování histaminu; Histamine Release; chemokin CXCL2; chemokin CCL1; Chemokine CXCL2; tick saliva; chemokine; Animals; ženské pohlaví; zvířata; Th2 response; Th2 Cells; myši inbrední C57BL; Chemokine CCL1; histamine; myši; Ixodes; Mice, Inbred C57BL; sliny; Th2 buňky; MCP-1; Mice; Female